2001
DOI: 10.1007/978-94-017-3674-9_64
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Sensitivity during Stem Elongation as an Avenue to Raise Potential Yield in Wheat

Abstract: Worldwide wheat yields have been only slightly, and non-significantly, increasing during the 90's, suggesting that they may be levelling off. Considering that there is consensus that large new growing areas will be not introduced and management improvements will be increasingly harder to obtain, genetic improvement would play a more important role to keep rising wheat yields in the future than in the past. In this scenario, the use of physiological bases as a complementary tool to identifying alternative ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 25 publications
5
75
0
6
Order By: Relevance
“…Due to this co-occurrence, the SE phase is considered to be critical for potential yield in wheat. This has been proposed quite early (Hudson 1934;Fischer 1985;Slafer et al 2001) and was widely confirmed in later years (Kirby 1988;Slafer et al 1996Slafer et al , 2001). Spike dry weight at anthesis is largely related to grain number per spike (Fischer 1985;Slafer et al 2001), which in turn has been found to be more yield determining than individual grain weight (Slafer et al 2001 and references cited therein), especially in connection with environmental variation of yield (Fischer 1985;Calviño and Monzon 2009).…”
Section: Physiological Backgroundmentioning
confidence: 72%
See 2 more Smart Citations
“…Due to this co-occurrence, the SE phase is considered to be critical for potential yield in wheat. This has been proposed quite early (Hudson 1934;Fischer 1985;Slafer et al 2001) and was widely confirmed in later years (Kirby 1988;Slafer et al 1996Slafer et al , 2001). Spike dry weight at anthesis is largely related to grain number per spike (Fischer 1985;Slafer et al 2001), which in turn has been found to be more yield determining than individual grain weight (Slafer et al 2001 and references cited therein), especially in connection with environmental variation of yield (Fischer 1985;Calviño and Monzon 2009).…”
Section: Physiological Backgroundmentioning
confidence: 72%
“…The number of fertile florets and the related spike dry weight depend on the duration of the SE and concurrent spike growth period (Slafer et al 1996(Slafer et al , 2001González et al 2003). It has been proposed that a prolonged SE phase would allow for more dry matter accumulation by the spike due to its longer growth phase, which would ultimately increase yield (Slafer et al 1996;Miralles and Slafer 2007;Whitechurch et al 2007).…”
Section: Physiological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Yields from current wheat cultivars containing RhtB1b or Rht-D1b alleles may be approaching their limits (Slafer et al, 2001), while a changing climate may reduce the usefulness of these genes in the future. These issues, combined with potential restrictions on the use of growth retardants and chemical fertilizer, highlight the need to develop novel dwarfing alleles.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of Vrn-H1 parallels the floral transition in barley (von Zitzewitz et al, 2005), and the expression of Vrn1 is required for the floral transition in wheat (Pearce et al, 2013). In contrast to vernalization, variations in photoperiod have minor effects on the duration of the vegetative phase but strongly accelerate the early and late reproductive phases of inflorescence development in wheat and barley Slafer et al, 2001). The duration of the spike growth phase has been identified as a major determinant of seed number (Fischer, 1985;Slafer, 2003;Reynolds et al, 2009;Alqudah and Schnurbusch, 2014) because of competition between the spike and stem for limited assimilates (González et al, 2003(González et al, , 2011Ghiglione et al, 2008).…”
Section: Introductionmentioning
confidence: 99%